Constitutively active androgen receptor splice variants expressed in castration-resistant prostate cancer require full-length androgen receptor - Watson, Philip A. (National Academy of Sciences, 2010)
Androgen receptor (AR) splice variants lacking the ligand binding domain (ARVs), originally isolated from prostate cancer cell lines derived from a single patient, are detected in normal and malignant human prostate tissue, with the highest levels observed in late stage, castration-resistant prostate cancer. The most studied variant (called AR-V7 or AR3) activates AR reporter genes in the absence of ligand and therefore, could play a role in castration resistance. To explore the range of potential ARVs, we screened additional human and murine prostate cancer models using conventional and next generation sequencing technologies and detected several structurally diverse AR isoforms. Some, like AR-V7/AR3, display gain of function, whereas others have dominant interfering activity. We also find that ARV expression increases acutely in response to androgen withdrawal, is suppressed by testosterone, and in some models, is coupled to full-length AR (AR-FL) mRNA production. As expected, constitutively active, ligand-independent ARVs such as AR-V7/AR3 are sufficient to confer anchorage-independent (in vitro) and castration-resistant (in vivo) growth. Surprisingly, this growth is blocked by ligand binding domain-targeted antiandrogens, such as MDV3100, or by selective siRNA silencing of AR-FL, indicating that the growth-promoting effects of ARVs are mediated through AR-FL. These data indicate that the increase in ARV expression in castrate-resistant prostate cancer is an acute response to castration rather than clonal expansion of castration or antiandrogen-resistant cells expressing gain of function ARVs, and furthermore, they provide a strategy to overcome ARV function in the clinic.